Streptomyces species: A friend or foe? the diagnostic dilemma of cutaneous and mucocutaneous infections - Archana Keche; Gargee Mishra; Girish Patil; Satyaki Ganguly; Swekcha Ranjan (Journal of Family Medicine and Primary Care, 2025)
Mycetoma and various invasive forms of the disease are caused by etiological agents like Nocardia, Actinomycetes, and Streptomyces spp. Streptomyces spp. is notable for its production of antibiotics. However, it is also most commonly associated with actinomycetoma, especially Streptomyces somaliensis (S. somaliensis), Streptomyces griseus. (S. griseus), S. sudanensis, and S. viridis. We present a series of cases with varied clinical presentations ranging from cutaneous nodules to plunging ranula in which Streptomyces spp have been isolated in culture with further species-level identification using MALDI-TOF.